Automated ice-sheet snowmelt detection using microwave radiometer measurements - Liang, Lei; Guo, Huadong; Li, Xinwu; Cheng, Xiao (Polar Research, 2013)
Monitoring ice-sheet snowmelt is fundamental to understanding global climate change. A simple and automated snowmelt detection process is critical to the establishment of an ice-sheet snowmelt monitoring system. However, different ice-sheet snowmelt detection methods are based on a variety of thresholding schemes using different melt signals for dry and wet snow; these complicate the regular operation of an ice-sheet snowmelt monitoring. We propose an automated melt signal detection method developed using melt signals derived from the cross-gradient polarization ratio snowmelt detection method over Greenland and the wavelet transformation-based snowmelt detection method over Antarctica. Initial results indicate that the proposed method not only increases computational efficiency, practicability and operability but is also more accurate. Keywords: Ice sheet; snowmelt detection; radiometer; cross-gradient polarization ratio; wavelet transformation; generalized Gaussian model.
Keywords: Antarktis; innlandsis; klimaendringer; mikrobølge; målinger; polarområdene; radiometer; snøsmelting; statistisk analyse; temperatur måling

The water column as an attenuating factor of the UVR effects on bacteria from a coastal Antarctic marine environment - Hernández, Edgardo A; Ferreyra, Gustavo A; Ruberto, Lucas A M; Mac Cormack, Walter P (Polar Research, 2009)
The effect of UVR on the viability of the culturable bacterial community fraction (CBC), and two of their isolated components (Arthrobacter-UVvi and Bizionia-UVps), was studied in the top few metres of the water column at Potter Cove, King George Island, Antarctica. Quartz flasks containing CBC from surface waters were exposed to solar radiation at depths of 0, 1 and 3 m. Similar experiments using UVps and UVvi isolates were performed. In some experiments interferential filters were used to discriminate photosynthetic active radiation (PAR), UV-A and UV-B. CBC from depths of 0, 10 and 30 m were also exposed to surface solar radiation. The deleterious effect of UVR was observed at the surface and at a depth of 1 m, but not at a depth of 3 m. Studies with interferential filters showed low bacterial viability values at depths of 0 and 1 m under both UVR treatments. However, under low radiation doses the effect attributed to UV-B was higher than that caused by UV-A. The surface CBC was more resistant to UVR compared with CBC from a depth of 30 m. The results showed that CBC inhabiting waters above the pycnocline (located at a depth of 5–10 m) are more efficiently adapted to UVR than are those from below the pycnocline. The impact of UVR on the marine bacterioplankton studied was only detected in the first metre of the stratified water column of Potter Cove, which has high levels of suspended particulate matter. These results support the evidence for a significant UVR-attenuating effect in the water column of this coastal Antarctic water.
Keywords: Sørishavet; UV-stråling; bakterier; marin biologi; plankton; statistisk analyse; ultrafiolett stråling; vannsøyle